Buddhist Paradoxical Logic as an Epistemological Method to the Ultimate Knowledge: From Dharmakirti’s Svavacanavirodha to Nishida’s Logic of Absolute Self-Contradiction - Galuh Nur Fattah (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025)
This article comprehensively explains the structure of Buddhist logic in explaining or describing the highest knowledge. The highest knowledge (Maha Prajñā) in question is knowledge of Nirvana (Pāli: Nibbāna). Buddhism describes Nirvana through paradoxical logic which, when viewed from the perspective of deductive logic in the Western logical tradition, is certainly invalid and often even concluded to be a fallacy. Although considered invalid or even a fallacy, Buddhist paradoxical logic has a functional mode, namely as a transcendental effort to optionally remove obstacles that arise from the mind and ultimately be able to directly experience the most authentic reality. This is what is called the highest knowledge. In solving this work, a conceptual analysis method was carried out with a literature study research model. From the results of the search and analysis, it was found that paradoxical logic is often present in classical Buddhist texts such as the Prajñā Pāramitā Hṛdaya Sūtra and Laṅkāvatāra Sūtra. This logic was later structured by Dharmakirti as a method of debate and referred to as Svavacanavirodha. In contemporary Eastern philosophical studies, this logic influences the logic of absolute self-contradiction or concrete logic (gutaiteki ronri) developed by Nishida Kitarō as an attempt to understand the nature of reality. In spiritual application, this logic can be developed as a method to liberate oneself from mental disturbances that can hinder the development of the intuitive dimension, thus making enlightenment more attainable.